Training and Assistance Model: Designing and Applying Blended Learning for Teachers of SMP Muhammadiyah XIV Pondok Pesantren Karangasem Lamongan - Swasti, Ika Korika; Artanto, Aphief Tri (Nusantara Science and Technology Proceedings, 2020)
The purpose of this training and mentoring is to transfer the development of learning media to strengthen e-learning based on information and communication technology (ICT). Solving the needs of partners is done with strategies, namely: empowering teachers to create ICT-based learning media, lectures on blended learning, and platforms. e-learning media. Practice making blended learning teaching media. The approach used is Participatory Rural Appraisal by involving UPNV JT community service implementers as facilitators or resource persons. The training participants are five teachers who are assisted and trained as cadres, then the knowledge is shared with other teachers to be implemented in learning. Assistance after training is still carried out online. After the training and mentoring were carried out, the teachers of SMP Muhammadiyah 14 Pondok Pesantren Karangasem Lamongan who were trained to design and implement blended learning: (a) have increased their knowledge regarding the understanding and implementation of blended learning; (b) has been able to convert PPT into visual learning media using Movavi software; (c) can use the equipment owned (laptop; smartphone), and perform editing using Movavi. The learning media used by the teacher can motivate students to learn repeatedly and is not limited by time and space.